A Certainty Equivalent Framework for Analyzing Risk Preferences in Organizational and Personal Decision-Making - Irvan Novikri; Noer Azam Achsani; Roy H.M. Sembel; Tony Irawan; Tubagus Haryono (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Decision-making under uncertainty remains a critical challenge in both organizational and personal contexts. Misunderstanding the differences between uncertainty, variability, ambiguity, and risk often leads to inaccurate risk assessments and biased decisions. Objective: This study examines risk attitudes and their influence on decision-making by clarifying conceptual distinctions among uncertainty-related conditions and evaluating their implications for effective risk management. Methods: This study applies a systematic literature review by synthesizing foundational and contemporary studies on decision analysis and risk attitudes. The analysis employs the Certainty Equivalent (CE) framework to classify risk preferences and examines the influence of cognitive biases on decision quality. Results: The findings indicate that the CE framework effectively differentiates risk-neutral, risk-averse, and risk-seeking behaviors based on preferences toward uncertain outcomes. Comparative analysis shows that excessive risk aversion or risk-seeking behavior can reduce long-term financial outcomes, while organizational incentive structures may encourage risk preferences that conflict with optimal strategies. Conclusion: This study concludes that aligning individual and organizational risk attitudes is essential for improving decision quality. The Certainty Equivalent framework provides a practical approach for diagnosing and calibrating risk preferences, while future research should validate the framework through empirical studies across diverse industries.